ANALISIS FAKTOR PERSEPSI RISIKO BENCANA GEMPA BUMI PADA MASYARAKAT Studi Kasus: Desa Langensari, Kecamatan Lembang - Prasetyawati, Endriana
Risk perception is an individual's assessment of the probability of an accident risk and understanding of the consequences received from the risk. Disaster risk perception is related to disaster preparedness which is a component in reducing disaster risks. Reducing disaster risks is needed especially in disaster-prone areas; one of them is Langensari, Kecamatan Lembang, which is prone to earthquake disasters caused by a fault called Lembang Fault. The aim of this research is to identify the factors affecting the risk perception the result of which will generate recommendation for disaster risk reduction based on public perception on earthquake risks. Data were collected by interviews, questionnaires and observation, while data analysis methodology used a qualitative data analysis; quantitative analysis utilized a spearman correlation analysis and chi-square correlation analysis. Based on the result of hazard identification, Langensari is an area which has a high level of earthquake disaster hazard based on the magnitude of earthquakes as a result of earthquake shock scenarios and the high acceleration value of rocks through calculation in a simulation using a shear wave velocity analysis (Vs30), high vulnerability based on the location which is prone to the movement of land as well as the majority of residential buildings which do not have retrofitting. The disaster capacity is still at a moderate level. As a tool for reducing disaster risks, risk perception is needed to interpret the community’s point of view against disasters. From the research result, 51% of total respondents perceive earthquake disaster risks as a high risk and 49% of respondents perceive earthquake disaster risks as a medium risk. After identifying factors which contribute to the perception of disaster risks, the researcher concludes that there is no variable found affecting the perception of disaster risks in aggregate but there are variables which affect the sub-variable of perception of disaster risks; these variables are both the outsider variable of disaster risk perception and the variable of disaster risk perception. Control of the risk, knowledge and experiences affected perceptions of the disaster’s impact and knowledge variable affected the level of voluntariness of the risk in the earthquake disaster.